Pig the star - Blabey, Aaron (New York Scholastic Press, 2018)
Pig the self-centered pug, and his friend Trevor, the Dachshund, are at a photo-shoot, and as usual, Pig wants to hog all the costumes and be the star of the show, but the photographer favors Trevor, and Pig needs to learn a lesson about sharing the spotlight.
"First published in Australia in 2017 by Scholastic Press, an imprint of Scholastic Australia Pty Ltd."
1.7
P-2
Keywords: Pug -- Juvenile fiction; Dachshunds -- Juvenile fiction; Dogs -- Juvenile fiction; Photographers -- Juvenile fiction; Sharing -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Pug -- Fiction; Dachshunds -- Fiction; Dogs -- Fiction; Photographers -- Fiction; Sharing -- Fiction; Stories in rhyme; Pug -- Fiction; Dachshunds -- Fiction; Dogs -- Fiction; Photographers -- Fiction; Sharing -- Fiction